The effects of augmenting traditional rehabilitation with audio biofeedback in people with persistent imbalance following mild traumatic brain injury - Campbell, Kody R.; Peterka, Robert J.; Fino, Peter C.; Parrington, Lucy; Wilhelm, Jennifer L.; Pettigrew, Natalie C.; King, Laurie A. (Frontiers in Neurology, 2022)
Complaints of non-resolving imbalance are common in individuals with chronic mild traumatic brain injury (mTBI). Vestibular rehabilitation therapy may be beneficial for this population. Additionally, wearable sensors can enable biofeedback, specifically audio biofeedback (ABF), and aid in retraining balance control mechanisms in people with balance impairments. In this study, we described the effectiveness of vestibular rehabilitation therapy with and without ABF to improve balance in people with chronic mTBI. Participants (n = 31; females = 22; mean age = 40.9 ± 11 y) with chronic (>3 months) mTBI symptoms of self-reported imbalance were randomized into vestibular rehabilitation with ABF (n = 16) or without ABF (n = 15). The intervention was a standard vestibular rehabilitation, with or without ABF, for 45 min biweekly for 6 weeks. The ABF intervention involved a smartphone that provided auditory feedback when postural sway was outside of predetermined equilibrium parameters. Participant's completed the Post-Concussion Symptom Scale (PCSS). Balance was assessed with the sensory organization test (SOT) and the Central Sensorimotor Integration test which measured sensory weighting, motor activation, and time delay with sway evoked by surface and/or visual surround tilts. Effect sizes (Hedge's G) were calculated on the change between pre-and post-rehabilitation scores. Both groups demonstrated similar medium effect-sized decreases in PCSS and large increases in SOT composite scores after rehabilitation. Effect sizes were minimal for increasing sensory weighting for both groups. The with ABF group showed a trend of larger effect sizes in increasing motor activation (with ABF = 0.75, without ABF = 0.22) and in decreasing time delay (with ABF = −0.77, without ABF = −0.52) relative to the without ABF group. Current clinical practice focuses primarily on sensory weighting. However, the evaluation and utilization of motor activation factors in vestibular rehabilitation, potentially with ABF, may provide a more complete assessment of recovery and improve outcomes.